Strong antiferromagnetism in isolated anionic dicopper(II) methanoato paddle-wheel complex - Kozlevčar, Bojan (Array, 2009)
Summary: A new ionic compound (C5H6NO)2 [Cu2 (μ-O2 CH)4 (O2CH)2], 1 formed of 4-hydroxypyridinium cations and a complex anion was synthesized. The anion is a paddle-wheel dicoppercarboxylate complex with four syn,syn-bridging and two axial anionic methanoato ligands. The XRD structure determination of 1 reveals that the molecular structure is stabilized by two H-bonds between the cations and the axial paddle-wheel anions (N–H---O 2.755(3), O–H---O 2.489(2) Å). The compound exhibits a very strong (2J = 500 cm–1) intra-binuclear antiferromagnetic interaction noticed already at room temperature attributed to the methanoato intra-binuclear bridges. The typical EPR S = 1 spin system signals of the dicopper paddle-wheel complexes at 90 and 450–700 mT are found in the room temperature spectrum, but they are poorly seen in the 110 K spectrum. These signals are of very low intensity and are accompanied by a dominant signal at 320 mT, all closely related to a very strong antiferromagnetic interaction present in 1